Antithrombotic therapy for a case report of acute myocardial infarction after laparoscopic radical cystectomy - Wang, Zilong; Yuan, Huisheng; Chu, Junhao; Duan, Shishuai; Zhang, Zhihui; Song, Changze; Wang, Muwen (Frontiers in Pharmacology, 2025)
BackgroundRadical cystectomy constitutes the standard therapeutic approach for high-risk urothelial carcinomas of the bladder. Contemporary guidelines advise urologists to discontinue anticoagulation therapy during the perioperative period to mitigate the risk of significant intraoperative or postoperative hemorrhage. Nevertheless, in elderly patients with a history of coronary artery disease, the cessation of anticoagulant medication elevates the risk of acute myocardial infarction, thereby posing a substantial threat to their survival. Therefore, the necessity and optimal strategy for anticoagulation therapy in patients with acute myocardial infarction following radical cystectomy remains a subject of ongoing debate. This study aims to contribute clinical insights for clinicians to manage high-risk patients with acute myocardial infarction post-major surgery.Methods and resultsThe 64-year-old male patient was admitted for multiple high-grade urothelial carcinomas of the bladder. The preoperative computed tomography angiography revealed intra-luminal stenosis of the coronary arteries. However, the patient declined further assessment via preoperative coronary angiography, thereby precluding the accurate prediction of postoperative myocardial infarction risk. The patient subsequently underwent laparoscopic radical cystectomy with Bricker conduit urinary diversion and the postoperative pathological examination confirmed the diagnosis of high-grade urothelial carcinoma (T1N0M0, G3). Regrettably, on the first postoperative day, the patient experienced an acute anterior wall ST-segment elevation myocardial infarction. Consequently, the patient underwent emergency percutaneous coronary intervention and was administered dual antiplatelet therapy consisting of aspirin and ticagrelor. The daily pelvic fluid drainage, routine blood and coagulation parameters remained within normal ranges. Following the second percutaneous coronary intervention and dual antiplatelet therapy, the patient was discharged after 2 days. Over a 3-year follow-up period, all hematological parameters consistently remained within normal ranges, and there were no incidents of bleeding or anastomotic leakage.ConclusionThis study demonstrates that postoperative percutaneous coronary intervention, in conjunction with continued dual antiplatelet therapy, is a safe and effective antithrombotic strategy for managing perioperative acute myocardial infarction. This finding suggests a potential paradigm shift in the management of antithrombotic therapy for high-risk surgical patients, advocating for a tailored approach rather than the routine discontinuation of such therapy.